Takhrij and Syarah Hadith of Agrotechnology How to take care of land fertility for cultivation - Meisya Nabila Poetri; Wahyudin Darmalaksana; Rani Widiana (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith on how to treat land fertility for farming. The research method used is a qualitative type through literature and field studies with the approach of takhrij and sharah hadith. The results and discussion of this research is fertile soil is land that when planted can produce high yields throughout the year. The conclusion of this study is that the takhrij and syarah hadith of agrotechnology provide information on the urgency of how to care for land fertility for farming where the value of soil fertility can be estimated by observing the physical, chemical, and biological properties of the soil.